Cervical Cancer in Botswana: Current State and Future Steps for Screening and Treatment Programs - Grover, Surbhi; Raesima, Mmakgomo; Bvochora-Nsingo, Memory; Chiyapo, Sebathu P.; Balang, Dawn; Tapela, Neo; Balogun, Onyinye; Kayembe, Mukendi K. A.; Russell, Anthony H.; Monare, Barati; Tanyala, Senate; Bhat, Jailakshmi; et al. (Frontiers in Oncology, 2015)
Botswana has a high burden of cervical cancer due to a limited screening program and high HIV prevalence. About 60% of the cervical cancer patients are HIV positive; most present with advanced cervical disease. Through initiatives by the Botswana Ministry of Health and various strategic partnerships, strides have been made in treatment of pre-invasive and invasive cancer. The See and Treat program for cervical cancer is expanding throughout the country. Starting in 2015, school-going girls will be vaccinated against HPV. In regards to treatment of invasive cancer, a multi-disciplinary clinic has been initiated at the main oncology hospital to streamline care. However, challenges remain such as delays in treatment, lack of trained human personnel, limited follow up care and little patient education. Despite improvements in the care of pre-invasive and invasive cervical cancer patients, for declines in cervical cancer related morbidity and mortality to be achieved, Botswana needs to continue to invest in decreasing the burden of disease and improving patient outcomes of patients with cervical cancer.